Environmental Uncertainty and Information Asymmetry: Does Conservative Financial Reporting Moderates the Results - Fatima, Huma (iRASD Journal of Economics, 2023)
Abstract: This research work examines the effect of uncertainty on information asymmetry moderated by conservative financial reporting Asymmetric information (spread), whereas uncertainty is calculated using a measure of the environmental scanning method. This method divides the sample into ‘inert’ and ‘alert’. ‘Inert’ firms are not scanning the environment, and ‘alert’ for firms who are constantly engaged in observing and scanning their environment while the coefficient of variation in sales is applied for robustness check of environmental uncertainty. A proxy developed by Khan and Watts is applied for accounting conservatism. The sample size of this research is taken from firms registered on the Pakistan Stock Exchange while the time period of study is 2010 to 2021. The statistical output reinforces the hypothesis of the study. The statistical results are evidence that conservative financial reporting may be helpful to reduce asymmetric information during uncertainty. Empirical estimations provide implications for all stakeholders e.g. investors, regulatory authorities, and researchers.